Access to the Sea for Developing Land-Locked States. - Glassner, Martin Ira (Nijhoff, 1970)
SCSU Faculty Scholar Award
Keywords: Access to the sea (International law); Landlocked states; Developing countries; Commerce; award_winner; dept.egm; faculty_collection

Nationalism in Early American Geographies: 1784-1845 - Antonelli, Michael F. (Journal of Geography, 1970)
There existed clear demonstrations of nationalism in geography textbooks written by Americans during two significant epochs in the history of the United States. Geographies regarded the environment, people or institutions of the United States either with extreme adulation or subtle pride. They viewed the nation favorably when its strengths and weaknesses were compared to each other or to foreign elements, even when objective evidence did not support such an assessment. And, finally, they reached a host of young and impressionable Americans, and instilled in them a fervor for their country. © 1970 Taylor and Francis Group, LLC.
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970G254500010 tex.unique-id: [object Object]
Keywords: dept.egm

Chibchas - History and Re-Evaluation - Glassner, M (Americas, 1970)
2 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1970ZK65900005
Keywords: dept.egm

Foreign Relations of Jamaica and Trinidad and Tobago, 1960-1965 - Glassner, MI (Caribbean Studies, 1970)
tex.unique-id: ISI:A1970Y377500005
Keywords: dept.egm; ⛔ No DOI found

Rio-Lauca - Dispute Over an International River - Glassner, MI (Geographical Review, 1970)
5 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1970F585800003
Keywords: dept.egm